2012
DOI: 10.11613/bm.2012.011
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility, accuracy and concordance of Accutrend® Plus for measuring circulating lipid concentration in adults

Abstract: IntroductionThe determination of lipid biomarkers by capillary sampling may be useful in the screening, diagnosis and/or personal management of hyperlipidemia and cardiovascular risk. It remains unclear whether the use of the Accutrend® Plus system is appropriate. This study aimed to assess its reproducibility, accuracy and concordance for blood lipid profiling in adults.Materials and methods:Fasting capillary total cholesterol (TC) and triglyceride (TG) concentration on Accutrend® Plus were compared with thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
1
24
1
1
Order By: Relevance
“…The intra assay precision of Accutrend ® Plus, as determined by the manufacturer, was 3.7% and 3.4% for TC and TG respectively. The inter-assay precision for Accutrend ® Plus determined with control solution by the manufacturer was lower than 5.0% for TC and 2.4% for TG [20].…”
Section: Lipids and Lipoproteinsmentioning
confidence: 81%
“…The intra assay precision of Accutrend ® Plus, as determined by the manufacturer, was 3.7% and 3.4% for TC and TG respectively. The inter-assay precision for Accutrend ® Plus determined with control solution by the manufacturer was lower than 5.0% for TC and 2.4% for TG [20].…”
Section: Lipids and Lipoproteinsmentioning
confidence: 81%
“…Evidence shows that the concordance to classify subjects according to their triglyceride levels of Accutrend is low compared with the standard laboratory methods. 31 We thus lowered the SSB selection cutoff to > 250 kcal/day in October 2009. Literature suggests that adults consuming > 250 kcal/day of SSBs can realistically reduce consumption anywhere from 100 to 150 kcal/day.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, Mendez-González et al (2009) found that the error rate for the Accutrend Plus device exceeded NCEP recommendations for total cholesterol but fell below it for triglycerides. Scafoglieri et al (2012) found that the concordance between methods for at-risk subject classification was not adequate according to the NCEP recommendations. The differences between our findings in the present study and the findings of Mendez-González et al and Scafoglieri et al may be at least partially explained by methodological differences, including sample size, criteria for categorization of blood variables, and statistical analysis procedures.…”
Section: Discussionmentioning
confidence: 97%